ChM. Dr. Wan Norfazilah invents environmentally friendly waterproof spray for fabrics - Nur Hartini, Mohd Hatta (2022)
PEKAN, 15 June 2022 - There are many waterproof spray products for fabrics, but most of the raw material solvents used are toxic, harming human health and the environment.